Prospective, Randomized Controlled Pivotal Trial of Biodegradable Balloon Rectal Spacer for Prostate Radiation Therapy - Song, Daniel; Dabkowski, Mateusz; Costa, Paulo; Nurani, Rizwan; Kos, Michael; Vanneste, Ben; Magel, David; Sapir, Eli; Zimberg, Shawn; Boychak, Oleksandr; Soffen, Edward; Alhasso, Abdulla; et al. (International journal of radiation oncology, biology, physics, 2024)
Rectal spacers have been shown to reduce rectal side effects in patients receiving prostate radiation. However, concerns remain regarding precise and reproducible gel injection. We evaluated efficacy and safety of a novel rectoprostatic spacer balloon that allows potential for controlled, adaptable deployment. This study tested co-primary hypotheses: (1) balloon spacer would result in ≥25% reduction of rectal V70 in >75% of subjects and (2) implantation procedure-related and rectal ≥grade 1 adverse events within 6 months (duration ≥2 days, Common Terminology Criteria for Adverse Events 4.0) would be noninferior in balloon versus control subjects. A total of 222 subjects were enrolled at 16 centers. All patients had T1-T3 prostate cancer without magnetic resonance imaging evidence of posterior extraprostatic invasion. Randomization was 2:1 (balloon: control) and subject-blinded. Patients underwent transperineal transrectal ultrasound axial and sagittal-guided fiducial placement ± balloon, followed by Intensity-Modulated Radiation Therapy (81 Gy in 1.8 Gy fractions or biologically equivalent hypofractionated dose). For efficacy comparisons, plans were generated by a central core lab on pre- and postimplant computed tomography scans. The primary efficacy endpoint was met, with 97.9% of balloon subjects (139/142) having rectal V70 reduction >25% (P < .001). Mean V70 was 7.0 % pre- versus 1.1% postimplant. The primary safety endpoint was met with balloon subjects experiencing fewer ≥grade 1 events, 18% versus 23% (P < .001 for noninferiority). On predefined secondary endpoint of ≥grade 2 events, rates trended lower in balloon subjects (4.3% vs 6.5%, P = .527). Mean perirectal spacing was 19 ± 3.7 mm and maintained through radiation treatment (18 ± 3.9 mm). Balloon resorption was observed on 6-month computed tomography in 98.5% (133/135) of subjects. The Expanded Prostate Cancer Index quality of life instrument was collected throughout study, and did not differ statistically between the study arms. Biodegradable rectal spacer balloon was effective in significantly reducing dose to rectum, and associated with decreased cumulative rectal plus implantation-related adverse events. Balloon resorption was consistently observed by 6 months.